2011
DOI: 10.1002/ep.10459
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and thermodynamic studies of the biosorption of Cu(II) by Agaricus campestris

Abstract: Agaricus campestris was used as an adsorbent for the adsorption of Cu(II) ions in water. The adsorption process was carried out in a batch process and the effects of contact time, initial pH, initial Cu(II) ion concentration, adsorbent amount, and temperature on the adsorption were investigated. Kinetic calculation results from the recent experiments showed that the amount of adsorbed Cu(II) increased with increasing Cu(II) concentration, pH, temperature, contact time and with decreasing adsorbent amount. Pseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…The differing adsorption capacities in the bio-chars may be attributed to the different properties of each bio-char resulting from structure, functional groups, and surface distribution, etc. [10]. For example, higher H/C ratio in the bio-char structure means greater bio-char adsorption capacity [34], in accordance with the results in Table 1.…”
Section: Adsorption Isothermssupporting
confidence: 90%
See 1 more Smart Citation
“…The differing adsorption capacities in the bio-chars may be attributed to the different properties of each bio-char resulting from structure, functional groups, and surface distribution, etc. [10]. For example, higher H/C ratio in the bio-char structure means greater bio-char adsorption capacity [34], in accordance with the results in Table 1.…”
Section: Adsorption Isothermssupporting
confidence: 90%
“…4, there is a continuous increase in percentage Cr (VI) ion removal with increasing adsorbent concentration from 0.2 to 5.0 g/L because of the increasing availability of binding sites for complexation of chromium ions [23]. The increase in number of adsorption sites or surface area resulting from the higher adsorbent dose leads to a higher percentage of heavy metal removal [10,24]. However, the q e values for all adsorbents decreased with increasing adsorbent concentration due to competition between the ions to bind to the available adsorption sites of the adsorbent [25,26].…”
Section: Effect Of Adsorbent Dose On the Adsorption Processmentioning
confidence: 97%
“…Common methods include chemical precipitation [5], reverse osmosis [6], ion exchange [7], electro-dialysis [8], uptake [9] and biosorption [10]. However, these techniques have some disadvantages such as high cost, low efficiency, low selectivity, high-energy requirements, and sludge generation [11]. Compared to other methods, uptake is simple and effective [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…With higher initial Cu concentrations, two different species of the Agaricus genus of mushrooms were studied over the past three years. The research determined that Cu removal varied from 2 to 32 mg Cu/g mushroom with initial Cu concentrations of 20–250 ppm . To further increase the removal concentration of Cu, researchers have shown that waste sludge can remove up to 800 mg Cu/g sludge .…”
Section: Introductionmentioning
confidence: 99%